Creativity over Time and Space - Michel Serafinelli; Guido Tabellini (Institute of Labor Economics (IZA), 2019)
Creativity is often highly concentrated in time and space, and across different domains. What explains the formation and decay of clusters of creativity? In this paper we match data on thousands of notable individuals born in Europe between the XIth and the XIXth century with historical data on city institutions and population. Our main variable of interest is the number of famous creatives (scaled to local population) born in a city during a century, but we also look at famous immigrants (based on location of death). We first document several stylized facts: famous births and immigrants are spatially concentrated and clustered across disciplines, creative clusters are persistent but less than population, and spatial mobility has remained stable over the centuries. Next, we show that the emergence of city institutions protecting economic and political freedoms and promoting local autonomy facilitates the attraction and production of creative talent.
Keywords: R10; O10; J61; J24; 330; innovation; agglomeration; political institutions; immigration; gravity